Influence of indirect internal stakeholders in the performance of strategic projects: understanding the behavior of projects in universities in Bogotá - Muñoz Peña, Fernando Andrés (2019)
The purpose of this research is to discover the effect of the extent, engagement, and empowerment of indirect stakeholders on the performance of internal strategic projects through the moderating effect of complexity. This research was done in the city of Bogotá in public and private universities from a sample of 356 respondents. The system of statistical analysis used to test the hypothesis of the research was structural equation modelling (SEM). The findings carry theoretical implications for these bodies of knowledge in management: Project Management and Strategic Management. Stakeholder extent has a significant effect on Performance of internal strategic projects. Stakeholder engagement does not have a significant effect on performance of internal strategic projects. Stakeholder empowerment has a significant effect on Performance of internal strategic projects. Complexity is the moderating variable between stakeholder extent and stakeholder engagement on Performance of internal strategic projects. This paper’s originality is manifest in the variables used, and in its depth of analysis of a gap found in the literature related to indirect stakeholders.